Does Islamic finance industry lack a certain degree of credibility? / Aly Khorshid. - Khorshid, Aly (Universiti Teknologi Mara Selangor, 2016)
Islamic banking and finance sector risks losing a golden opportunity to demonstrate an alternative system that could prevent a future credit crunch and share risks. With the conventional banking sector slowly coming to terms with its high-profile collapses and bailouts, the Islamic sector has suffered only mild aftershocks. The question that comes to mind is: why are savers and investors not flocking to shariah-compliant banking? Could Islamic finance lack a certain degree of credibility? And if so, why?